[PP.05.11] DIABETES MELLITUS AND OBESITY IN THE FRENCH CARIBBEAN: A SPECIAL VULNERABILITY FOR WOMEN?. (September 2016) - Carrère, P.; Sportouch, D.; Hélène-Pelage, J.; Fagour, C.; Lang, T.; Inamo, J.
Abstract : Objective: In the Caribbean, both women and men have a high rate of early cardiovascular-linked mortality. Our objective was to analyze the characteristics of diabetes mellitus and its management in an adult population sample from the French Caribbean. Design and method: A multicenter cross-sectional study was conducted in Guadeloupe between July and December 2014, including all patients aged 18–74 receiving a systematic periodic health examination funded by social security. Sociodemographic, medical, anthropometric and biological data collection was standardized. Diabetes was defined by an antidiabetic treatment or fasting glucose > = 7 mmol/l and HbA1c > = 6.5%, and diabetes control was defined as HbA1c < 7%. Multilevel logistic regression was used to analyze the factors linked to diabetes. Results: 2252 participants were included (56.5% women). Diabetes prevalence was 8.2% for women versus 5% for men (p = 0.003). The proportion of women with diabetes aware of their condition was 84.5%, versus 67.4% in men (p = 0.016). Nearly all the diagnosed participants were being treated. In both sexes, diabetes control was obtained in less than a third of participants. 55.3% of women had a waist circumference equal to or above the NCEP thresholds, versus 14% of men (p < 0.001). In multivariate analysis, the OR of diabetes linked to female sex approached 1 when abdominal adiposity was taken into account in the model. Conclusions: In this French Caribbean population, obesity and diabetes mellitus greatly affected women. In spite of a good diabetes detection rate, diabetes was rarely controlled. A comprehensive women's health policy going beyond universal health coverage should be designed.